The effect of the level of indebtedness on the earnings information content stemming from the mandatory IFRS adoption - Turki, Hela; Wali, Senda; Boujelbene, Younes (International Journal of Accounting and Economics Studies, 2016)
This paper examines the impact of IFRS / IAS (International Financial Reporting Standards / International Accounting Standards) mandatory adoption on the earning's information content apprehended by the level of information asymmetry and whether this impact differs from one company to another with regard to its level of indebtedness. The information asymmetry is measured by the properties of financial analysts’ forecasts (error and dispersion).This study is conducted over 11 years from 2002 to 2012 by taking as a sample all the companies that belong to the CAC all tradable indexes. The results show a significant effect of these international's standards on financial analysts' forecasts, which stress informational content improvement. In addition, high level of indebtedness associated with IFRS adoption reduces forecast dispersion. By contrast, low level of indebtedness associated with IFRS adoption reduces forecast error.
Keywords: IFRS; Financial Analysts’ Forecasts; Level of Indebtedness.